Cooperative learning through placemat to promote critical reading skill: what are efl learners' views? - Zahratul Idami; Wahidah; Dessy Kurniasy; Shafrida Wati (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Cooperative Learning as an approach in the EFL classroom seems applicable and effective. However, learners' perception is essential to consider to adjust the application of this approach in the classroom to reach the learning objectives. Therefore, this research aimed to determine EFL learners' views toward using Cooperative Learning through Placemat to promote critical reading skills. This research used a qualitative design with 32 EFL learners from Tarbiyah and the Teacher Training Faculty of the Institute of Islamic Studies Langsa, Aceh, as the subject. A set of questionnaires and an interview were administered as the instrument to collect the data. In addition, this research found that EFL learners have a positive view regarding using Placemat as a medium in applying Cooperative Learning in English Foreign Language Classroom, especially in reading class. Thus, this research contributes to the addition of literature in EFL teaching and learning by suggesting cooperative media to be used.